2009
DOI: 10.1083/jcb1875oia11
|View full text |Cite
|
Sign up to set email alerts
|

GATA-3 is required for early T lineage progenitor development

Abstract: Most T lymphocytes appear to arise from very rare early T lineage progenitors (ETPs) in the thymus, but the transcriptional programs that specify ETP generation are not completely known. The transcription factor GATA-3 is required for the development of T lymphocytes at multiple late differentiation steps as well as for the development of thymic natural killer cells. However, a role for GATA-3 before the double-negative (DN) 3 stage of T cell development has to date been obscured both by the developmental hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(89 citation statements)
references
References 50 publications
(97 reference statements)
5
83
0
1
Order By: Relevance
“…GATA3 expression increases from the ETP to DN3 stages of T cell development. GATA3 hypomorphic mutant embryos, adoptive transfer of GATA3-null hematopoietic stem cells (HSC) and mice conditionally deleted for GATA3, conclusively showed that GATA3 is required for the development of functional ETPs (23). Recent work confirmed the requirement for GATA3 at the transition from DN1 to DN2 and its essential role in promoting a Notch-induced T cell program.…”
Section: Tsp To Dn2 Stagesmentioning
confidence: 67%
“…GATA3 expression increases from the ETP to DN3 stages of T cell development. GATA3 hypomorphic mutant embryos, adoptive transfer of GATA3-null hematopoietic stem cells (HSC) and mice conditionally deleted for GATA3, conclusively showed that GATA3 is required for the development of functional ETPs (23). Recent work confirmed the requirement for GATA3 at the transition from DN1 to DN2 and its essential role in promoting a Notch-induced T cell program.…”
Section: Tsp To Dn2 Stagesmentioning
confidence: 67%
“…While we do not wish to imply that Notch signaling is no longer involved in further T cell differentiation (as also discussed further in this review), it does illustrate that other molecular mechanisms might be more important for driving further developmental progression. This may involve the activity of critical T-lineage transcription factors such as TCF-1, GATA-3 and BCL11b (Verbeek et al, 1995;Weber et al, 2011;Ting et al, 1996;Taghon et al, 2001;Taghon et al, 2007;Hosoya et al, 2009;Li et al, 2010a;Li et al, 2010b;Ikawa et al, 2010). Such mechanisms might also be recruited to silence the Notch target genes DTX1 and NRARP, while the Notch signaling activity itself, as measured by the amount of ICN that is released, remains at its initial signaling strength.…”
Section: Induction Of T-cell Commitmentmentioning
confidence: 99%
“…Gata1 is required for the proper maturation of erythroid, mast and megakaryocytic precursors, and for the specification of eosinophils, whereas Gata2 is necessary for mast cell development and for the maintenance and expansion of hematopoietic stem cells (Fujiwara et al, 2004;Ohneda and Yamamoto, 2002). Gata3 is required for the development of T lymphocytes (Hosoya et al, 2009). Other critical factors in hematopoiesis are Rag1, which is essential for the differentiation of T and B lymphocytes (Petrie-Hanson et al, 2009), and Runx1, which regulates the formation of hematopoietic progenitors, myeloid cells and the vasculature (Jin et al, 2012;KalevZylinska et al, 2002).…”
Section: Introductionmentioning
confidence: 99%